Pandangan Hukum Islam Tentang Sewa-menyewa Tanah Dengan Sistem Pembayaran Panen - Ikmal, Ikmal; Rahman, Arif (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2022)
This journal discusses "Islamic legal views on land rent with a harvest payment system in Patte'ne village, Takalar district". Leasing is included in the law of engagement because in a lease there are at least two parties who enter into an agreement, one party states that he is able to give something and the other party binds himself in an agreement to help each other meet their respective needs. Likewise with the prevailing custom in Patte'ne Village, Takalar Regency, they often hold land lease transactions with a harvest payment system, so it is detrimental to the tenants because the payment system is not clear. This research was conducted by field research or empirical juridical research. With a sociological juridical approach and a statutory approach. The sources of data in this study, namely: Primary data, secondary data and searches of various literatures or references. Data collection methods used are observation, interviews, and documentation. Data processing and analysis techniques are carried out through three stages, namely: data identification, data reduction, and data editing. This type of research is a field research using a normative descriptive method. normative descriptive research is research that aims to accurately describe the characteristics of a particular thing, individual, symptom, situation or group. Based on the research used above, it can be concluded that in the implementation of the contract carried out verbally there is no written agreement between the two parties based on mutual trust with one another and they enter into a land lease transaction with a harvest payment system so it is detrimental to the tenant because the payment system is not clear, in the event of a disaster or loss then this is the responsibility of both parties. The implementation of the land lease in Patte'ne Village, Takalar Regency does not meet the requirements in the land lease contract.